Endoscopic mucosal resection for flat neoplasia in chronic ulcerative colitis: can we change the endoscopic management paradigm?. Issue 6 (29th November 2006) - Hurlstone, David P; Sanders, David S; Atkinson, Robert; Hunter, Michael D; McAlindon, M E; Lobo, A J; Cross, Simon S; Thomson, Mike
Abstract : Background: The potential of endoscopic mucosal resection (EMR) for treating flat dysplastic lesions in chronic ulcerative colitis (CUC) has not been addressed so far. Historically, such lesions were referred for colectomy. Furthermore, there are only limited data to support endoscopic resection of exophytic adenoma-like mass (ALM) lesions in colitis. Aims: To evaluate the safety and clinical outcomes of patients with colitis undergoing EMR for Paris class 0–II and class I ALM compared with sporadic controls. Secondary aims were to re-evaluate the prevalence, anatomical "mapping" and histopathological characteristics of both Paris class 0–II and class I lesions in the context of CUC. Methods: Prospective clinical, pathological and outcome data of patients with colitis-associated Paris class 0–II and Paris class I ALM treated with EMR (primary end points being colorectal cancer development, resection efficacy, metachronous lesion rates and post-resection recurrence rates) were compared with those of sporadic controls. Results: 204 lesions were diagnosed in 169 patients during the study period: 167 (82%) diagnosed at "entry" colonoscopy, and 36 (18%) diagnosed at follow-up. 170 ALMs, 18 dysplasia-associated lesion masses (DALMs) and 16 cancers were diagnosed. A total of 4316 colonoscopies were performed throughout the study period (median per patient: 6; range: 1–8). The median follow-up period for the complete cohort was 4.1 years (range: 3.6–5.21). 1675 controls were included from our prospective database of patients without CUC who had undergone EMR for sporadic Paris class 0–II and snare polypectomy of Paris type I lesions from 1998 onwards, and were considered to be at moderate to high lifetime risk of colorectal cancer. 3792 colonoscopies were performed throughout the study period in this group (median per patient: 4; range: 1–7). The median follow-up period was 4.8 years (range: 2.9–5.2). No statistically significant differences were observed between the CUC study group and controls with respect to age, sex, median number of colonoscopies per patient, median follow-up duration, post-resection complications, median lesional diameter or interval cancer rates. However, there was a significant between-group difference regarding the prevalence of Paris class 0–II lesions in the CUC group (82/155 (61%)) compared with controls (285/801 (35%); χ 2 = 31.13; p<0.001). Furthermore, recurrence rates of lateral spreading tumours were higher in the colitis cohort (1/7 (14%)) than among controls (0/10 (0%); p = 0.048 (95% CI 11.64% to 40.21%)). Conclusions: Flat DALM, similarly to Paris class I ALM, can be managed safely by EMR in CUC. A change in management paradigm to include EMR for the resection of flat dysplastic lesions in selected cases is proposed.